The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.20884/1.anprod.2016.18.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Red Betel Leaf (Piper crocatum) in Dairy Cattle Feed on Fermentation Characteristics by in Vitro

Abstract: The aim of this study was to assess the impact and efficiency of red betel leaf’s extract supplementation in the diet of dairy cattle on fermentation characteristics by in vitro.  The research method was experiment by using completely randomized design.  The treatments that were tested were R1: basal feed, R2:  R1 + 15 ppm of  red betel  leaf (Piper crocatum) extract, R3: R1 + 30 ppm of  red betel leaf (Piper crocatum) extract, R4: R1 + 45 ppm of red betel leaf (Piper crocatum) extract, R5: R1 + 60 ppm of red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
2
0
0
1
Order By: Relevance
“…The results of this study showed that the addition of leaf betel extract affected highly significantly (P<0.01) on OMD in the feed of dairy cattle, in similar pattern as it did on DMD (Table 1). Similarly Prayitno et al (2014) found identical responds compared to this study; the decrease in DMD was followed by the decrease in OMD and vice versa. In line with the two cases, Prayitno and Hidayat (2013) stated that the degradation of OM a close relationship with the degradation of DM.…”
Section: Organic Matter Digestibilitysupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study showed that the addition of leaf betel extract affected highly significantly (P<0.01) on OMD in the feed of dairy cattle, in similar pattern as it did on DMD (Table 1). Similarly Prayitno et al (2014) found identical responds compared to this study; the decrease in DMD was followed by the decrease in OMD and vice versa. In line with the two cases, Prayitno and Hidayat (2013) stated that the degradation of OM a close relationship with the degradation of DM.…”
Section: Organic Matter Digestibilitysupporting
confidence: 86%
“…The means of VFAP ranged from 93.5 to 164 mM (Table 1). The results of Prayitno et al (2014) showed that the means of TVFA were approximately equal, namely 86.40-187.40 mM compared to the addition of red betel leaf extract in this study. The decrease of TVFAP was assumed to be due to the secondary metabolites in the red betel leaf extract in the forms of flavonoids (myricetine) that are capable of suppressing the microorganisms that produce the TVFA.…”
Section: Total Volatile Fatty Acid Productionsupporting
confidence: 44%
“…Maior digestibilidade da matéria seca e matéria orgânica; e redução da produção de metano (CH 4 ) em função do uso do extrato vegetal rico em miricitrina na dieta de vacas leiteiras 49 .…”
Section: Miricitrinaunclassified